CALCULATION RETAINING WALLS OF LAND FOR HANDLING LANDSLIDES ROAD SECTION TERAJUK-TEMULA NYUATAN DISTRICT WEST KUTAI - Dikok, Yakobus (KURVA S JURNAL MAHASISWA, 2014)
West Kutai district which is salasatu which has abundant natural resources,sustainable management of management needed so that people can continue togrow and thrive both in terms of economic, social and cultural. West KutaiDistrict continue to make efforts to improve themselves in order to pursue otherareas in Indonesia, which has succeeded in the development of the region. With alarge area, supported by abundant natural resources, then the public should beable to enjoy the West Kutai welfare and prosperity in various fields.Landslide that occurred on the road that experienced landslides, must beaddressed so that it does not interfere with and harm the environment and if it isleft unchecked will eat erosion or scour resulting in a reduction in the crosssection of the road.Handling avalanches due to erosion on the road, of course, require theexistence of analysis and technical studies, detailed and comprehensive, so it canproduce a design that is appropriate and effective in order to conform with theoriginal purpose of the handling of avalanches can be achieved.From the calculation results can be concluded that the dimensions of theland pehanan wall is 3.5 meters high and 1 meter wide body length of 10 metersper segment. Secure the stability of a retaining wall to bolster however affect theshear, so that the necessary foundation piles with additional bracing to the pilegroup to rigidify the structure of the walls and the pile.